2022
DOI: 10.3390/foods11223658
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Hemp (Cannabis sativa L.) Inflorescences as Novel Food: The Effect of Different Agronomical Practices on Chemical Profile

Abstract: In this study, the effect of several agronomical practices on the chemical composition of hemp inflorescences, a potential novel food that needs to be further studied, was observed. Here, the case study of inflorescences from Ferimon cultivars is discussed and submitted to different agronomical practices (irrigation and fertilizers) in different years, and the inflorescences harvested in different periods were analyzed by a multimethodological approach. Targeted and untargeted methodologies allowed cannabinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…The same trend was observed for all the individual cannabinoids except CBG, which in 2019 was found at levels significantly lower compared to 2020. These results are in line with those reported by Spano and co-authors [30], who found a major influence of cropping year on cannabinoid accumulation compared to harvesting stage and fertilization. Furthermore, meaningful differences in the cannabinoid content between two years of cultivation were observed in the essential oil, although these were not statistically significant according to the ANOVA analysis [33].…”
Section: Variation In Phytochemical Content and Antioxidant Activity ...supporting
confidence: 93%
See 1 more Smart Citation
“…The same trend was observed for all the individual cannabinoids except CBG, which in 2019 was found at levels significantly lower compared to 2020. These results are in line with those reported by Spano and co-authors [30], who found a major influence of cropping year on cannabinoid accumulation compared to harvesting stage and fertilization. Furthermore, meaningful differences in the cannabinoid content between two years of cultivation were observed in the essential oil, although these were not statistically significant according to the ANOVA analysis [33].…”
Section: Variation In Phytochemical Content and Antioxidant Activity ...supporting
confidence: 93%
“…Therefore, understanding the effect of these factors on the accumulation of phytochemical compounds is crucial to obtaining inflorescences enriched with valuable compounds and with high commercial value. To date, several studies have been carried out on the effects of specific agronomical practices, harvesting stages, and storage conditions on the phytochemical composition of hemp inflorescences [26][27][28][29][30], whereas the effects of genotype and cropping season have been poorly investigated. Therefore, the objective of this study was to gain insights for the first time into the effect of genotype, year, and their interaction on the accumulation of secondary metabolites and the antioxidant activity in C. sativa inflorescences.…”
Section: Introductionmentioning
confidence: 99%
“…The CP content of quinoa inflorescences was higher (25.09 g) compared to those found in other inflorescences such as Moringa oleifera (20.48 g), torch ginger (12.6 g), and banana (15.82 g/100 g, DW) [26,34,35]. However, on a fresh weight (FW) basis (about 80% moisture content), much lower CPs were reported in other inflorescences such as rape and cabbage (4.19-4.40 g) and fennel (1.37 g/100 g, FW) [29,33]. The fat content of quinoa inflorescences, 2.80 g/100 g on a dry weight basis, exceeded that of Moringa oleifera (1.83 g) and banana (0.6 g).…”
Section: Proximate Analysismentioning
confidence: 99%
“…Previous studies have investigated the nutritional content of flowers and inflorescences from various plant species, including banana [29], coconut [30], cocoyam [31], fennel [32], industrial hemp [33], moringa [34,35], rape and cabbage [36], and torch ginger [37], and revealed a diverse array of nutrients, vitamins, minerals, bioactive components, and nutraceuticals. However, there remains limited information regarding the nutritional profile of quinoa inflorescences.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above, it is important to preserve their desired sensory characteristics during the drying process. Many papers have been published describing the effect of drying on the composition of secondary metabolites of hemp inflorescences [13][14][15].…”
Section: Introductionmentioning
confidence: 99%